On the comparison of changes induced in crystallinity and surface nanomechanical properties of ultra high molecular weight polyethylene by γ and swift heavy ion irradiations - Lagarde, Mayra (2014)
In this work the influence of two different irradiation techniques on the degree of crystallinity and nanomechanical properties of a medical grade UHMWPE is compared. One technique, widely used in the production of components for total joint replacement, is comprised by γ-irradiation followed by a thermal treatment above the melting temperature of UHMWPE and thus modifies the material's bulk. The other one, an alternative modification technique that affects only the near surface layers of UHMWPE, is swift heavy ion (SHI) irradiation. The effect of two types of ion beams (nitrogen and lithium) with different energies (33 and 47 MeV) and fluences (1011 to 1013 ions/cm2) is investigated. Changes in degree of crystallinity are investigated by DSC and Raman spectroscopy while the nanomechanical properties – elastic modulus and hardness – are evaluated by nanoindentation tests. The γ-irradiated and remelted sample exhibits lower degree of crystallinity than the pristine material due to the hindered recrystallization process of the crosslinked chains. Concomitantly, this sample shows a reduction in hardness and elastic modulus of the bulk. On the other hand, SHI-irradiated samples display a large increase in degree of crystallinity and surface mechanical parameters with respect to pristine UHMWPE. The modification is confined to the ion target depth. The layer affected by the ion beam shows constant mechanical properties that appeared to be slightly influenced by the fluence in the studied range (around the optimum). Despite the changes induced by both techniques are completely different, they are able to enhance the wear performance of UHMWPE due to the beneficial change in elastic to plastic properties. Among SHI-irradiated samples, the N-ion (33 MeV and 1 × 1012 ions/cm2) exhibits the better combination of nanomechanical properties.